Students’ Proficiency Of Cultural Values In Literature-Based Reading Materials: An Experimental Study - Primasari, Yusniarsi; Sari, Hesty Puspita (Penerbit Widina, Widina Media Utama, 2025)
This study explores the impact of literature-based reading instruction on students’ ability to identify cultural values in texts. Conducted with 17 second-semester students at Balitar Islamic University, it employed a one-group pre-test post-test design. Participants engaged in three learning sessions using varied literary genres (novels, comics, and storybooks). Statistical tests (Shapiro-Wilk, Levene’s, and paired-sample t-test) indicated significant improvement in post-test scores (p 0.05). The instruction enhanced cultural literacy and reading skills, notably in vocabulary acquisition, identifying main ideas, and recognizing supporting details. However, students showed limited progress in inferring moral lessons or implied meanings. These findings highlight the pedagogical value of integrating literature into English as a Foreign Language (EFL) programs to promote intercultural awareness and responsive reading in higher education.ABSTRAKPenelitian ini mengeksplorasi dampak pembelajaran membaca berbasis sastra terhadap kemampuan mahasiswa dalam mengenali nilai budaya dalam teks. Melibatkan 17 mahasiswa semester dua di Universitas Islam Balitar, studi ini menggunakan desain pre-test post-test satu kelompok. Mahasiswa mengikuti tiga sesi pembelajaran dengan berbagai genre sastra seperti novel, komik, dan cerita anak. Analisis data menggunakan uji statistic termasuk uji normalitas Shapiro-Wilk, uji homogenitas Levene, dan uji-t sampel berpasangan menunjukkan adanya peningkatan signifikan kemampuan membaca (p 0,05). Pembelajaran berbasis sastra terbukti meningkatkan penguasaan kosakata, identifikasi gagasan utama, dan detail pendukung. Namun, peningkatan dalam menyimpulkan nilai moral atau makna tersirat masih terbatas. Temuan ini menegaskan pentingnya integrasi sastra dalam pembelajaran Bahasa Inggris sebagai Bahasa Asing (EFL) untuk meningkatkan literasi budaya dan membaca responsif di pendidikan tinggi.